Self-realization as a Driver of Sustainable Social Development: Balancing Individual Goals and Collective Values - Stoliarchuk, Olesia; Yang, Qi; Diedkov, Mykola; Serhieienkova, Oksana; Ishchuk, Alla; Kokhanova, Olena; Patlaichuk, Oksana (European Journal of Sustainable Development, 2024)
Self-realization is integral to the social aspect of sustainable development, as it enables individuals to boost mental health and personal well-being by achieving and enhancing their potential and life goals. This study explores how self-realization functions as a driver for sustainable social development in the face of adversity. The research, which involved 122 adult Ukrainians, utilized written surveys, statistical analysis, qualitative assessment, and ranking to collect data. Despite the persistent threats and crises, Ukrainians exhibit significant motivation and engagement in self-realization across various domains, including professional endeavors, family interactions, and parenting. The wartime environment has introduced new dimensions to self-realization, such as involvement in volunteering and charitable activities. Key areas of self-realization include professional and family roles, which highlight the effectiveness of personal fulfillment. Nonetheless, respondents encounter common challenges, such as procrastination, laziness, and emotional strain. The majority acknowledge the connection between their self-realization and sustainable social development, particularly its social dimensions. While self-actualization is essential for life fulfillment during the ongoing conflict in Ukraine, it necessitates targeted psychological support to tackle individual-specific challenges. Self-actualization remains a vital process for life fulfillment in wartime Ukraine, yet it requires targeted psychological support to address individual challenges. Keywords: self-realization, personality, development, societal sustainable development, social component of societal sustainable development, adult personality, communication